In vitro differentiation of Trypanosoma cruzi epimastigotes into metacyclic trypomastigotes using a biphasic medium - Jessica Rodríguez Durán; Arturo Muñoz-Calderón; Karina Andrea Gómez; Mariana Potenza (STAR Protocols, 2021)
Summary: The pathogen Trypanosoma cruzi differentiates from epimastigotes (E) into infective metacyclic trypomastigotes (MTs) to invade the mammalian cell. This process, called metacyclogenesis, is mimicked in vitro by nutrient starvation or incubation with minimal media. Here, we describe an alternative protocol for metacyclogenesis by incubating E forms in a biphasic medium supplemented with human blood. Although time consuming, this procedure yields fully differentiated MTs without the presence of intermediate forms, even for cultures that have been maintained as E for years.